ANALISA PENGARUH VOLUMETRIC LOADING RATE TERHADAP PENURUNAN PARAMETER COD PADA REAKTOR UASB DALAM PENGOLAHAN LIMBAH CAIR DOMESTIK PERUMAHAN MUNJUL JAYA PURWAKARTA: ANALISA PENGARUH VOLUMETRIC LOADING RATE TERHADAP PENURUNAN PARAMETER COD PADA REAKTOR UASB DALAM PENGOLAHAN LIMBAH CAIR DOMESTIK PERUMAHAN MUNJUL JAYA PURWAKARTA - Nur Ilman Ilyas (Jurnal Pelita Teknologi, 2019)
Domestic waste which come from WC, i.e black water as well as other sources domestic waste has potensial to polute the environment because this waste has caracteristics high in COD. The purpose of this study is to find the concentration of artificial waste. if the concentration of the polutan is high, the load of the polutan in the waste also high. In this study Mixture of artificial grey water and black water were investigated. This Mixture consist of COD. This research investigated the organic loading rate and to treating the Mixture Grey Water and Black Water with reactor UASB. The decreasing Conentration of organic loading rate small varied, COD was about 644 mg/l..